FORMULATION AND EVALUATION IN VITRO A MATRIX TYPE OF KETOTIFEN FUMARATE TRANSDERMAL PATCHES FOR ALLERGIC DISEASES - Hamdan, Lama; Husian, Jamila (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: Transdermal patches of Ketotifen fumarate (KT) were developed for prolonged effect of the drug, and to protect the patient from allergic symptoms associated with asthma and other allergic diseases. Methods: Matrix type patches were prepared by solvent casting technique using different types of polymers: Hydroxy propyl methyl cellulose (HPMC K15M) and ethyl cellulose to formed the matrix of the patch in different ratios, emulsifying agents were added as a penetration enhancers (Span 60, Tween 60, Cremophor EL) in a ratio 0.025% w/v to the matrix, 10% v/v of glycerin was added as plasticizer to 10 ml of chloroform:methanol (1:1). The drug matrix film was casted on a polyvinyl alcohol backing membrane. All patches were evaluated for physical proprieties, thickness uniformity, folding endurance, moisture uptake, moisture content, drug content, uniformity of weight, content uniformity, in vitro drug release, and kinetic models. Differential scanning calorimetry was used to characterize physical mixtures of KT and the different used excipients. Results: The results showed that the prepared patches had acceptable physical properties. The drug substance was released well. Adding the penetration enhancers delayed the release of the drug from the matrix in all the prepared formulas, formula A2 that having no enhancer, showed maximum amounts of drugs release (90.06Â±0.9)% for 24 hrs. However, adding penetration enhancers decreased the amount of the drug release, formula B2 having Tween 60 as a penetration enhancer, showed the maximum release of the drug (87.78Â±0.88)%, and formula B3 having Cremophor EL showed the minimum release of the drug (79.13Â±1.58) at the end of 24 hrs dissolution study. The release of the drug from all formulations was followed by Korsmeyer-Peppas pattern with n>0.45 indicating that drug release from matrix was mainly happened by swallowed and diffusion (non- Fickian pattern). Conclusion: Optimized formula A2 containing the maximum amounts of HPMC K15M showed a controlled release of the drug over 12 hrs, and it identified as a successful formulation for this study.